2022
DOI: 10.1186/s41938-022-00516-8
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic and growth-promoting potential of multifarious bacterial endophytes against Fusarium wilt of chickpea

Abstract: Background Chickpea is the most important legume crop in India, and its productivity is significantly lowered due to biotic constraints such as wilt caused by Fusarium oxysporum f. sp. ciceris. Endophytes help plants to thrive better under stress conditions by regulating plant hormones and inducing systemic resistance. The aim of the present study was to identify chickpea root bacterial endophytes having antagonistic ability for the management of the Fusarium wilt. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Niu et al [62] and Danish et al [6] had demonstrated earlier the induction of drought tolerance in plants using rhizosphere microbes. The observed increase in the maize seed germination rate was consistent with earlier reports, which support the use of microbial agents, singularly or combined with other agents, to mediate physiological changes and improve crop growth [66,67].…”
Section: Discussionsupporting
confidence: 91%
“…Niu et al [62] and Danish et al [6] had demonstrated earlier the induction of drought tolerance in plants using rhizosphere microbes. The observed increase in the maize seed germination rate was consistent with earlier reports, which support the use of microbial agents, singularly or combined with other agents, to mediate physiological changes and improve crop growth [66,67].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we focused on antagonistic bacteria inside the leaves of diseased plants. In fact, many studies have focused on the biocontrol antagonists isolated from healthy plants [31,32], but few on those from diseased leaf parts. Therefore, it is of great interest to isolate cultivable antagonistic bacteria from diseased plants.…”
Section: Discussionmentioning
confidence: 99%
“…It also supports the plant by making iron easily available for various biological processes operating inside the plant system. Numerous recent studies reported siderophore production as the most common trait in bacterial endophytes associated with plants [ 69 , 70 , 71 , 72 ]. Apart from plant growth promoting traits, another mechanism that bacterial endophytes employ to combat fungal plant pathogens is the synthesis of extracellular hydrolytic enzymes [ 73 ].…”
Section: Discussionmentioning
confidence: 99%